2013
DOI: 10.1080/00071668.2013.778389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary rosemary and oregano volatile oil mixture on quail performance, egg traits and egg oxidative stability

Abstract: 1. This study was conducted to determine the effects of volatile oil mixture on quail laying performance, egg traits and egg malondialdehyde (MDA) concentration. 2. A total of 260 Pharaoh quails (Coturnix coturnix Pharaoh) aged 6 weeks were equally divided into 5 groups of 65 (4 replicates of 13 quails each). The mixture of diets was as follows: a control treatment with 0 mg volatile oil/kg of diet; (1) 200 mg/kg rosemary volatile oil; (2) 200 mg/kg oregano volatile oil; (3) 40 mg/kg rosemary volatile oil plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Şimşek et al (2015) reported that there was no difference in egg production, egg weight, feed intake and feed conversion ratio in the group supplemented with 200 mg/kg of rosemary essential oil compared to the control group, but dietary supplementation of rosemary essential oil was increased eggshell thickness in laying quails. Yeşilbağ et al (2013) reported that the dietary rosemary oil supplementation (at a level of 200 mg/kg) did not affect body weight, egg weight, egg mass, egg shell thickness or egg shell breaking strength of quails. There was no difference on feed intake of treatment groups and the inclusion of rosemary essential oil numerically improved the feed efficiency, but not statistically.…”
Section: Resultsmentioning
confidence: 97%
“…Şimşek et al (2015) reported that there was no difference in egg production, egg weight, feed intake and feed conversion ratio in the group supplemented with 200 mg/kg of rosemary essential oil compared to the control group, but dietary supplementation of rosemary essential oil was increased eggshell thickness in laying quails. Yeşilbağ et al (2013) reported that the dietary rosemary oil supplementation (at a level of 200 mg/kg) did not affect body weight, egg weight, egg mass, egg shell thickness or egg shell breaking strength of quails. There was no difference on feed intake of treatment groups and the inclusion of rosemary essential oil numerically improved the feed efficiency, but not statistically.…”
Section: Resultsmentioning
confidence: 97%
“…The RO has been used previously as a preservative in the human food industry due to its antioxidant and antimicrobial activities (Raskovic et al, 2014). Different amounts of supplementation of RO prevents HS-induced decreases in growth performance and carcass traits of Japanese quail (Ç iftç i et al, 2013) and, also improves growth performance, egg traits, egg oxidative stability, and meat quality of Pharaoh quail reared in TN environmental conditions (Yesilbag et al, 2013). Different constituents (terpenoids, flavonoids, phenolic acids, volatile oils) of rosemary have been reported to function by decreasing oxidative stress in different tissues of mammals that is induced by different chemicals (Tanyıldızı et al, 2009;Singh et al, 2012;Raskovic et al, 2014) or that is produced as a result of exposure to electromagnetic field (Hajhosseini et al, 2013).…”
Section: Alleviating Effects Of Romentioning
confidence: 99%
“…Rosemary ( Rosmarinus officinalis L.) is a native plant of the Mediterranean countries widely used as aromatic and medicinal plant (Charles, ) having antioxidant proprieties (Carvalho, Moura, Rosa, & Meireles, ; Okoh, Sadimenko, & Afolayan, ; Yesilbag, Gezen, Biricik, & Meral, ). The high antioxidant activity was related with phenolic diterpenes (carnasol, rosmanol, 7‐methyl‐epirosmanol, isorosmanol, and carnosoic acid) and phenolic acids (rosmarinic and caffeic acids) (Alagawany & El‐Hack, ; Yesilbag, Eren, Agel, Kovanlikaya, & Balci, ).…”
Section: Introductionmentioning
confidence: 99%